Microbiology : pretest, self-assessment and review - Tilton, Richard C. (New York : McGraw Hill Education, 1985)
This book meets the criteria established by the AMMA's department of continuing medical examination for up to 22 hours nof credit in category 5d for the physician's recognition award.
Virology -- Bacteriology -- Physiology -- Rickettsiae, chlaydiae, and mycoplasmas -- Mycology -- Parasitology -- Immunology.
Includes bibliographical references.
Keywords: MICROBIOLOGY -- REVIEW, SELF-ASSESSMENT, PRETEST